Extraction Optimization of Pigeon Pea Seed Protein and Yield Using Response Surface Methodology - Indriati, Sri; Yusuf, Muhammad; Irsal, Muhammad; Latief, Mahyati; Umar, Nuraeni; Usdyana Attahmid, Nur Fitriani (Politeknik Negeri Ujung Pandang, 2022)
Pigeon Pea (Casanus Cajan L.) is one of the local foods in South Sulawesi. Pigeon pea seeds contain protein that the body can absorb. This study aims to determine the optimum operating conditions for extracting pigeon pea on protein and yield using Ultrasonic-Assisted Extraction (UAE). Response Surface Methodology (RSM) with Box-Behnken Design (BBD) was used by considering three variables, time (30, 40, and 50 min), temperature (40, 50, and 60oC), and methanol concentration (50, 70, and 90%). The experiment results show that yield ranges from 8.85663% to 31.4766% and 46.1538 mg/l to 15584.6 mg/l. Response variables were computed and used to create the contour plot graphs. The optimum operating conditions for sonication extraction were a time of 44.760 minutes, a temperature of 60oC, and a 90% methanol concentration.